Imaging Findings of Pelvic Tumor Thrombosis Extending from Sacral Bone Metastasis of Adrenocortical Carcinoma. (26th December 2012) - Ishida, Kenichiro; Inoue, Yusuke; Woodhams, Reiko; Asano, Yuji; Hara, Toshimasa
Abstract : We report the imaging findings of a patient with adrenocortical carcinoma who showed pelvic tumor thrombosis extending from sacral bone metastasis. Contrast-enhanced computed tomography demonstrated extensive intraluminal filling defects in the pelvic veins. A lytic lesion in the sacrum was also noted and continuity between the sacral lesion and the filling defect in the branch of pelvic veins was indicated. The filling defects showed increased uptake on positron emission tomography with 18 F-fluorodeoxyglucose and single-photon emission computed tomography with 131 I-iodomethylnorcholesterol, and fusion images with computed tomography aided the localization of the increased uptake areas. Multimodality imaging may be beneficial for the characterization and localization of lesions in patients suspected of having metastatic adrenocortical carcinoma.